Spices rack with braille / Muhammad Amer Hakim Zamzaimi … [et al.] - Zamzaimi, Muhammad Amer Hakim; Junaidi, Mohamad Kamal Aiman; Raja Azni, Raja Nur Ayuni Fitrina; Rebuan, Fatin Nur Syuhada; Anuar, Nur Adriana Shahirah; Jamil, Muhammad Fairuz (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The visually impaired community faces significant challenges in the kitchen, where the lack of accessible tools and equipment hinders their ability to cook safely and independently. This extended abstract presents a business proposal for the Spice Rack Braille, a unique solution designed to address the accessibility needs of the visually impaired in the kitchen. The kitchen environment poses numerous obstacles for the visually impaired, particularly in identifying spices and ingredients due to inadequate labeling systems. This leads to difficulties in meal preparation, potential safety hazards, and a lack of independence in cooking activities. To Identify the specific challenges faced by the visually impaired in the kitchen environment. The Spice Rack Braille introduces a novel approach to addressing the accessibility needs of the visually impaired in the kitchen. By incorporating Braille labeling on spice bottles, this solution offers a tactile and user-friendly method for spice identification, setting it apart from existing products in the market. By giving visually impaired people the confidence and independence to cook, the Spice Rack Braille has the potential to make a big difference in their lives. This product makes the kitchen more accessible, which increases efficiency and safety while also giving users a feeling of empowerment and inclusion. With a niche market and increasing demand for inclusive and accessible products, the Spice Rack Braille offers a promising commercialization opportunity. The product presents a feasible business opportunity because it has the potential to appeal to both individual consumers and institutional buyers, such as assisted living facilities and organizations that support the visually impaired.